Examining The Relationships Between Work Intensification, Work-Life Balance, Employee Engagement And Turnover Intention Through A Gender Lens: The Perspective Of Academics In Malaysian Public And Private Universities - Goo, Chuan Chiew (2018)
The Malaysian government has recently reformed the public and private universities in order to transform Malaysia into a world-class higher education hub. The rapidly growing work demands among academics in public and private universities has caused academic work intensification. Thus, the effects of work intensification on other aspects of work such as work-life balance, coping strategies, employee engagement and turnover intention in the higher education sector are pertinent for further research. This study applied the theory of Job Demand-Resources and Social Role Theory to test the relationships between work intensification, work-life balance and turnover intention among academics in Malaysian public and private universities through a gender lens. The moderating effect of employee engagement on the relationship between work intensification, work-life balance and turnover intention was also explored. This study employed sequential explanatory design of mixed-method approach whereby the qualitative results are used to assist in explaining and interpreting the findings of the quantitative study. Quantitative data were collected through a survey from 190 respondents in public and private universities in Malaysia whereas the qualitative data were collected through semi-structured interviews with 12 academics (6 academics were from public universities and 6 academics were from private universities).